PENGGUNAAN TABLEAU SERVER SEBAGAI MANAJEMEN VISUALISASI DATA DI KAPANLAGI YOUNIVERSE - Bifakhlina, Febriyanti (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
KapanLagi Youniverse is an information agency as well as an online media company that has 10 different types of online media with varying segments from one another. Being an information institution, KLY must be able to manage data and information for millions of its users every day. One of the obtainable data from KLY is pageviews, which comes from Google Analytics for websites that are on KLY. Pageviews data for KLY reaches trillions of requests/users and must be managed or disseminated for stakeholders. This can help KLY data team and managers to provide decisions and related insights from existing data. n order to make managing and pageviews data more attainable, Tableau Server is used. Tableau will help visualize the widely used business intelligence data on KapanLagi Youniverse.